2000
DOI: 10.1007/s11627-000-0045-z
|View full text |Cite
|
Sign up to set email alerts
|

Anatomy of normal and hyperhydric leaves and shoots of in vitro grown Simmondsia chinesis (link) schn

Abstract: The anatomy of normal and hyperhydric in vitro shoots and leaves from micropropagated Simmondsia chinensis (Link.) Schn. (jojoba) was compared with that of seedlings (control plants). In vitro normal plantlets displayed good development and survived during the acclimatization stage. In vitro hyperhydric plantlets presented numerous anatomical defects, such as hypertrophy of the mesophyll and of the stem cortex, malformed non-functional stomata, epidermal discontinuity, and xylem hypolignification; they did not… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
20
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 39 publications
(22 citation statements)
references
References 11 publications
(15 reference statements)
2
20
0
Order By: Relevance
“…The microchemical testing on transverse sections of the stems of the hyperhydric plantlets of Simmondsia chinensis (Link), revealing that there was scarce lignification and that xylem organisation was poor (Apóstolo and LLorente, 2000). We suggest that in some way BA affects the metabolism of phenolics, majorly lignins or their precursors, and the lack of this important heteropolymer turns the vascular cell wall weak, less hydrophobic, and permeable to water, causing hyperhydricity.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…The microchemical testing on transverse sections of the stems of the hyperhydric plantlets of Simmondsia chinensis (Link), revealing that there was scarce lignification and that xylem organisation was poor (Apóstolo and LLorente, 2000). We suggest that in some way BA affects the metabolism of phenolics, majorly lignins or their precursors, and the lack of this important heteropolymer turns the vascular cell wall weak, less hydrophobic, and permeable to water, causing hyperhydricity.…”
Section: Discussionmentioning
confidence: 84%
“…chinensis (Link) showed that leaves had very thin cuticles and malformed stomata at the epidermal level (Apóstolo and LLorente, 2000). In the hyperhydric leaves of carnation Majada et al (2001) stated that, although the stomata had ellipsoidal guard cells sited at the same level as the epidermal cells, some stomata were raised above the leaf surface, supported on the epidermal cells.…”
Section: Discussionmentioning
confidence: 99%
“…5), probably because photosynthetic rate is too low or exogenous sucrose cause a negative feedback on plastidic enzymes for starch biosynthesis (Krapp and Stitt 1994). The anatomy of in vitro microshoot leaves, such as reduced mesophyll differentiation and thin cuticle with scarce wax deposition, exhibited typical features described in other in vitro plants (Johansson et al 1992, Apóstolo andLlorente 2000). The nursery plant leaves had both, a thick and well developed palisade parenchyma that according to Costa et al (2009) indicates an adaptation to greater PFD.…”
Section: Discussionmentioning
confidence: 93%
“…Hyperhydric in vitro plants of Datura insignis (Fontes et al 1999), Capsicum annuum (Fontes et al 1999), and Simmondsia chinensis (Apóstolo and Llorente 2000) showed deformation of the guard-cell walls, possibly due to loss of elasticity or to modifications in the pattern of cellulose microfibril deposits (Ziv and Ariel 1992;Picoli et al 2001;Ziv and Chen 2008). These deformations were not found in the hyperhydric leaves of H. impetiginosus.…”
Section: Discussionmentioning
confidence: 99%